Agresivitas Pajak, Environmental Performance, Leverage dan Likuiditas, terhadap Corporate Social Responsibility Disclosure dengan Profitabilitas sebagai Pemoderasi - Januar Eky Pambudi; Hendra Galuh Febrianto; Solikhatun Annisa; Selvitriana Selvitriana (Universitas Jember, 2024)
The focus of this study is the company's lack of attention and awareness of social responsibility, which results in conflicts between companies and communities regarding the impact of company operations. This shows that there are multiple factors that influence corporate social responsibility. The purpose of this research is to find out how tax aggressiveness, environmental protection, leverage, and liquidity affect the disclosure of corporate social responsibility, with profitability as a moderator. This research was conducted on 19 consumer non-cyclic companies listed on the Indonesia Stock Exchange during the 2017-2021 period, using a purposive sampling technique. Data were analyzed using panel data regression using E-Views 12.0. The results show that tax aggressiveness has a significant negative effect on CSR disclosure, while leverage has a positive effect on CSR disclosure. Environmental protection and salary have no effect on CSR disclosure. Profitability cannot reduce tax aggressiveness, level of environmental protection, and disclosure of corporate social responsibility, but can strengthen or reduce the effect of liquidity on social responsibility. Keywords: Corporate Social Responsibility Disclosure, Tax Aggressiveness, Environmental Performance, Leverage, Liquidity, Profitability.